State Authority In The Digital Society And E-Commerce Regulation - Suryadi, Rohmad; Oktaviana, Lusi; Herwiyanto, Herwiyanto; Nurhayati, Nunik (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study critically analyzes the role of the state in the digital society through e-commerce policy, focusing on Indonesia’s Minister of Trade Regulation No. 31 of 2023. Using a normative juridical method with regulatory inventory, systematic legal norm analysis, legal interpretation, and normative evaluation approaches, the research examines how this regulation addresses the transformation of trade activities in the digital era. The findings reveal that the regulation affirms the state's dual role as regulator and protector within the digital ecosystem by stipulating business licensing requirements for domestic and foreign actors, enforcing consumer protection, implementing affirmative policies for MSMEs, regulating electronic advertising, and strengthening law enforcement against violations. The study’s novelty lies in its integrative analysis combining juridical and public policy perspectives, highlighting that effective e-commerce governance requires synergy between digital law frameworks, business actors’ digital literacy, and strengthened institutional capacity of the state to ensure an inclusive, fair, and sustainable digital ecosystem. It recommends enhancing business actors' literacy on digital legal compliance and bolstering state institutional capacities in supervision and enforcement to maximize the strategic objectives of e-commerce policies, thereby supporting Indonesia's digital sovereignty and economic transformation.